(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article examines the translation activity of the Uzbek Jadid intellectual, poet, prose writer, dramatist, publicist, and translator Abdulhamid Sulaymon o‘g‘li Cholpan, as well as his translations of works from world literature into the Uzbek language. In particular, the study analyzes Cholpan’s translation of the fable “The Wolf and the Lamb” by the renowned Russian fabulist I. Krylov, which occupies an important place in the history of Uzbek translation studies. The analysis focuses on the date of the translation, its sources, and key issues related to translation practices.